Inhotim e o contemporâneo permanente - Campana, Marcela Somensari (2018)
The present work is developed within the field of social sciences, although in reflection on an institution of art, the Instituto Inhotim. Tracing aspects in order to construct a history of the Institute, we draw a reflection on the space where it is located through a historical regression provided by the remnant elements of its past, contained in the present of its exhibition. The methodology that allowed this reflexive practice was the historical materialism reviewed by Walter Benjamin, to which the images allow breaking the continuum of history so that we can remember the past that is not counted in the official discourses. Therefore, we were able to understand Inhotim not only by the characteristics detailed by itself in its catalogues, books and interviews, but going beyond, in the aspects of its consolidation, building a paradoxical history that understands it as a worldwide transformation of contemporary art, as well as bringing to light contradictory aspects of its project, promoting the formation of a "constellation" for the understanding of the events, so that each one redraws its history. Here we construct a possible story about Inhotim, placing it as a heterotopy of our society, which reflects desires and ideals of it, while space is reconfigured within pretexts of access control, aesthetic perfection and pleasure. Simultaneously, we seek to reflect how this space builds a time, promoting an approximation to Benjamin's theory of history, to understand at our present the decline in the possibility of experiencing something because of a symbolic disruption of the historical constructions of things, in which we can’t understand the origin and therefore transmit values. Inhotim defines itself as an experience. In the light of Benjamin's thoughts we revisit this concept, contesting the possibility of, indeed, experiencing the space